2019
DOI: 10.1536/ihj.18-717
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Residual Stenosis on the Angiographic Edge Restenosis of a Second-Generation Drug-Eluting Stent

Abstract: Edge restenosis has gained attention as a main cause of restenosis after first-generation drug-eluting stent (DES) implantation. The aim of this study was to assess the incidence of edge restenosis and identify the predictors of edge restenosis after second-generation DES implantation. Data were obtained from several postmarketing surveillance (PMS) studies on a cobalt-chromium everolimus-eluting stent (CoCr-EES; Xience V/ PROMUS, Xience Prime, Xience Prime SV, and Xience Expedition SV), a second-generation DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, normal coronary angiography has been reported for patients with cobalt poisoning (Samar et al 2015), and no signi cant difference was found in serum troponin levels (Berber et al 2017). Additionally, with the common use of cobalt in drug-eluting stents, no cases of cobalt poisoning have been reported (Kozuma et al 2019;Romaguera et al 2014;Sotomi et al 2018). However, another study has shown signi cantly increased serum enzymes and low voltages on ECG in patients with cobalt poisoning (Packer 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, normal coronary angiography has been reported for patients with cobalt poisoning (Samar et al 2015), and no signi cant difference was found in serum troponin levels (Berber et al 2017). Additionally, with the common use of cobalt in drug-eluting stents, no cases of cobalt poisoning have been reported (Kozuma et al 2019;Romaguera et al 2014;Sotomi et al 2018). However, another study has shown signi cantly increased serum enzymes and low voltages on ECG in patients with cobalt poisoning (Packer 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Stent norm-expansion is undoubtedly expected to have favorable outcomes, whereas under-expansion leads to unfavorable outcomes whether bare metal stents or DESs were used (Fujii et al, 2005;Nakamura et al, 2016). Numerous previous studies showed that immediate residual stenosis of ≤ 20% was acceptable (Kozuma et al, 2019;Watanabe et al, 2018) and was considered an angiographic success (Smith et al, 2006), because the cutoff point was associated with relatively lower rate of ISR and ST. However, an increasing amount of evidence indicated that postprocedural MLD was a key determinant of ISR (Kuntz et al, 1993).…”
Section: Discussionmentioning
confidence: 99%